Laparoscopy in Gynaecological Problems - Shamsa Tariq , Bushra Sultana , Noreen Majeed , Faraz Munir Butt (Journal of Rawalpindi Medical College, 2013)
and findings observed on laparoscopy in gynaecological conditions to assess the role of laparoscopy. Methods: In this cross sectional study 57 patients were included. Patients were in their reproductive age with history of lower abdominal pain for longer than six months. Laparoscopy was performed under general anesthesia. The uterine cannula was secured to the cervix after holding it by means of single toothed tenaculum. After induction of proper pneumo-peritoneum, laparoscopy was performed using an intra-umbilical or sub-umbilical entry. In subfertile patients 10 to 15ml of methylene blue dye solution was instilled and dye was inspected entering in the tubes and free spill through fimbrial end. Results: Major indication for laparoscopy was subfertility(75.43%). Majority (52.63%) belonged to primary subfertility. Six women(10.52%) were with chronic pelvic pain. Chronic ectopic pregnancy was suspected in 7.01% and lost IUCD in 7.01%. Mean age of the women was 31 years. Majority (52.63%) were nullipara.In primary subfertility group, tubal factor was found in 46.6% and ovarian factor in 16(53.33%). Normal pelvic findings were observed in 46.6%. Lost IUCD was found in four cases. No major complications were observed postoperatively. Patients were discharged on the next day of operation. Conclusion: Laparoscopy circumvents unnecessary surgeries and helps in making early diagnosis